Partnerships for affordable and equitable disaster insurance - Jaroslav Mysiak; C. D. Pérez-Blanco (Fondazione Eni Enrico Mattei (FEEM), 2015)
Extreme events are becoming more frequent and intense, inflating the economic damages and social hardship set-off by natural catastrophes. Amidst budgetary cuts, there is a growing concern on societies' ability to design solvent disaster recovery strategies, while addressing equity and affordability concerns. The participation of private sector along with public one through Public-Private Partnerships (PPPs) has gained on importance as a means to address these seemingly conflicting objectives through the provision of (catastrophic) natural hazard insurance. This is the case of many OECD countries, notably some EU Member States such as the United Kingdom and Spain. The EU legislator has adapted to this new scenario and recently produced major reforms in the legislation and regulation that govern the framework in which PPPs for (catastrophic) natural hazard insurance develop. This paper has a dual objective: 1) review the complex legal background that rules the provision of insurance against natural catastrophes in the EU after these major reforms; 2) assess the implications of the reforms and offer concise Policy Guiding Principles.
Keywords: Q54; Q58; G22; 330; Public-Private Partnerships (PPPs); Natural Hazards Insurance; Economic Instruments; Solidarity